Fire effects on soil microbial community structure and function in a ponderosa pine ecosystem - Jiménez Esquilin, Aida E., author; Stromberger, Mary, advisor; Butters, Gregory, committee member; Kelly, Eugene, committee member; Klein, Donald, committee member; Romme, William H., committee member (Colorado State University. Libraries, 2006)
Fires can cause drastic changes to the chemical and physical properties of forest soils. Depending on factors such as fire severity and intensity, these changes can be beneficial or detrimental to the soil microbial community. Because soil microbial community resurgence is crucial to the recovery of the forest ecosystem (due to the functional roles microorganisms have in soil stabilization and nutrient cycling, for example) it is important to improve our understanding of soil ecological responses to fire. Using three culture independent methods (EL-FAMEs, total microscopy counts and PCR-DGGE) to measure microbial community structure, and substrate induced respiration assays to measure microbial C and N mineralization activities, microbial response to fire was evaluated. Soil physicochemical properties were also measured. My results from microbial studies demonstrated that the rate of microbial community recovery, and thus rates of soil recovery differ depending on fire severity. Aerial hydromulching, ameliorated the effects of fire in AM fungi, but it did not hasten the recovery of soil bacteria. Also, potential microbial C and N mineralization activities had recovered in the moderate severity burn after 3 years. I also found that some negative long term-effects (21 years) of soil scarification can be ameliorated by a pine ecosystem. However, light severity fire and high severity fire had similar detrimental effects on microbial biovolumes and C and N mineralization activities. Arbuscular mycorrhizal fungi were negatively impacted throughout the study by fire regardless of severity as measured by concentrations of the fatty acid 16:1ω5c biomarker in soil. Aerial hydromulching, a post-fire erosion control treatment, acted to maintain greater water contents in burned soil, ameliorated the effects of fire in AM fungi, but it did not hasten the recovery of soil bacteria. Also, potential microbial C and N mineralization activities had recovered in the moderate severity burn after 3 years. I also found that some negative long term-effects (21 years) of soil scarification (e.g., reduced levels of soil C and organic matter (OM), lower biovolumes of both fungi and bacteria, and a shift in the microbial community towards one dominated by Grampositive EL-FAME markers) can be ameliorated by a high severity fire, presumably due to the increased OM, inorganic N and extractable P associated with a fire event. Although slash pile burning is an effective method for removal of unmarketable debris and small trees, it produces an extreme heat pulse into the soil which causes severe soil scorching. In my study on the effects of slash pile burning, I found that microbial activity had not recovered in burned soil 15 months after pile ignition. Initially, the microbial community structure was different at the edge of the pile compared to communities at the center of the pile where the fuel load and thus the heat load was larger. However, 15 months after the burn, microbial communities in burned soil were similar between the edge and center but were different from microbial communities from nonburned soil. This study showed that initial recovery dynamics were influenced by the fire intensity as shown by the differential response to location under the pile, but later the degree of recovery depended on the changes in soil properties such as nutrient content and pH of the burned soil. There were general trends among these studies, in particular regarding the lack of fungal resiliency to fire. In all studies, fungal biovolumes and/or activity proved to be more affected by fire than bacterial biovolumes and/or activity. I tested the hypotheses that 1) the short-term negative impact on fungal populations was due to higher pH of the soil after a fire or 2) because of early competition with bacteria (which showed to be more resistant than fungi). My data suggested that elevated pH may have a negative impact on fungal biovolumes and respiration, but contrary to what was expected, in high temperature heated soil fungi were positively affected by bacterial activity. I concluded that after a high temperature heating event, the dominant interaction between the two microbial groups is not competition but commensalism or synergism. Overall, these findings suggest that the dynamics of soil microbial recovery after a fire are not simple, and interactions exist among some of the components of the fire regime (fire severity, fire intensity, season of fire) that will affect the outcome of the soil recovery and therefore of the above ground community.
Keywords: soil sciences; microbiology